Implementasi Aksioma Etik Praktik Financing pada Lembaga Keuangan Mikro Syariah sebagai Upaya Mewujudkan Sustainable and Resposible Investment di Indonesia - Ningrum, Ririn Tri Puspita (WADIAH, 2018)
This research is motivated by the fact that the new direction of the concept of development in the world has accepted the concept of Sustainability Development Goals. This implies that all stakeholders involved in national development are required to be able to realize the objectives as contained in the concept, including the Islamic finance business. This business should have a future view. This orientation will encourage Islamic finance to continue to conduct research and development to find various types of needs and technology and other standards that are in line with future demands. It is interesting if the study relates to the implementation of axioms of ethics in realizing the Sustainability Development Goals concept in the Islamic finance business in Indonesia for further research. Through an empirical study with a qualitative approach, this study shows that conceptually, the Islamic microfinance institution agrees with the concept of green banking as a form of sharia compliance. While implementation, Islamic microfinance institutions in Indonesia have not significantly followed the components of green banking.